A porous carbon-supported metal oxide adsorbent and its preparation method and application

By loading metal oxides on porous carbon, an efficient porous carbon-loaded metal oxide adsorbent is formed, which solves the problem of low adsorption and degradation efficiency of porous carbon materials in the prior art, and achieves efficient removal of aniline in water and solid waste Resource utilization, low cost and easy industrialization.

CN115722188BActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111002938.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-30
Publication Date
2025-01-07
Estimated Expiration
2041-08-30

AI Technical Summary

Technical Problem

In the prior art, the adsorption and degradation efficiency of porous carbon materials using oil-containing solid residues as raw materials is low, and it is impossible to effectively treat light components in the sludge.

Method used

Porous carbon is prepared by pyrolyzing solid waste in the presence of zinc chloride, and metal oxides such as Fe, Co, Cu, Ni are loaded thereon to form porous carbon-loaded metal oxide adsorbent, and its specific surface area is controlled At 70-400m2/g, efficient removal of aniline in water bodies is achieved.

Benefits of technology

The specific surface area and pore volume of the adsorbent are improved, the degradation efficiency of aniline is significantly improved, the resource utilization of solid waste is realized, and the preparation cost is low, and it is easy to use in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115722188B_ABST
    Figure CN115722188B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of adsorbents, and discloses a porous carbon-loaded metal oxide adsorbent and a preparation method and application thereof. The adsorbent contains porous carbon and a metal oxide loaded on the porous carbon, wherein the porous carbon is obtained by pyrolyzing solid waste in the presence of zinc chloride, and the metal oxide is an oxide formed by at least one element of Fe, Co, Cu, and Ni; based on the total weight of the adsorbent, the content of the porous carbon is 88-95% by mass, and the content of the metal oxide is 2-8% by mass; the BET specific surface area of ​​the adsorbent is 70-400 m 2 / g. The adsorbent provided by the present invention has a large specific surface area and pore volume, can quickly and effectively catalyze and remove aniline in water, realizes resource utilization of solid waste, and has low preparation cost and is easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorbents, and in particular to a porous carbon-supported metal oxide adsorbent and a preparation method and application thereof. Background Art

[0002] Oily sludge (referred to as sludge) is one of the main pollutants in the petroleum industry. Its main components include aged crude oil, wax, asphaltene, colloids, suspended solids, bacteria, salts, acidic gases, corrosion products, and a large amount of flocculants, corrosion inhibitors, and scale inhibitors invested in the production process.

[0003] The output of oil sludge is closely related to the amount of crude oil produced and processed. The greater the amount of crude oil processed, the higher the oil sludge output. It is estimated that about 1 ton of oily sludge will be generated for every 200 tons of crude oil produced or processed. In 2016, the total amount of crude oil production and imports reached 600 million tons. Therefore, the annual output of oil sludge in my country is expected to reach 3 million tons.

[0004] With the development of economy and society, my country has intensified its efforts to treat and dispose of oil sludge. At present, the oil sludge is treated by thermal chemical washing and extraction technology to separate the light components from the oil sludge, and a certain amount of solid residue is produced at the same time. These solid residues have a high oil content and cannot be discharged directly. If they are simply buried, it will not only waste resources but also cause irreparable pollution to the environment.

[0005] CN111167408A discloses a method for preparing an adsorbent material from oily sludge residue, which specifically includes the following steps: soaking the oily sludge residue after pyrolysis of oily sludge in an ammonium salt solution for a certain period of time, then filtering, placing the filter cake in a tubular furnace, rapidly heating to 450-650°C under nitrogen protection, and carbonizing at a constant temperature for 1-6 hours to obtain a carbon adsorbent material. Although the above method can realize the resource utilization and harmless treatment of oily sludge, the adsorption and degradation efficiency of the adsorbent material is low. Summary of the invention

[0006] The purpose of the present invention is to overcome the defect of low adsorption and degradation efficiency of porous carbon materials using oil-containing solid residue as raw materials in the prior art.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a porous carbon-supported metal oxide adsorbent, which contains porous carbon and a metal oxide supported on the porous carbon, wherein the porous carbon is obtained by pyrolyzing solid waste in the presence of zinc chloride, and the metal oxide is an oxide formed by at least one element of Fe, Co, Cu, and Ni; based on the total weight of the adsorbent, the content of the porous carbon is 88-95% by mass, and the content of the metal oxide is 2-8% by mass; the BET specific surface area of ​​the adsorbent is 70-400 m2 / g.

[0008] A second aspect of the present invention provides a method for preparing a porous carbon-supported metal oxide adsorbent, the method comprising:

[0009] (1) subjecting solid waste and zinc chloride to a first contact mixing, and subjecting a first solid material obtained after the first contact mixing to a first pyrolysis to obtain porous carbon;

[0010] (2) contacting a metal salt solution with the porous carbon to perform an impregnation treatment, and performing solid-liquid separation on the impregnation mixture obtained after the impregnation treatment to obtain a solid impregnated product; wherein the metal element in the metal salt solution is selected from at least one of Fe, Co, Cu, and Ni;

[0011] (3) subjecting the solid impregnated material to a second pyrolysis and subjecting the second solid material obtained by the second pyrolysis to a molding process;

[0012] Wherein, the amount of the metal salt solution is such that the content of the metal oxide in the obtained porous carbon-supported metal oxide adsorbent is 2-8% by mass;

[0013] The conditions of the first pyrolysis and / or the second pyrolysis are controlled so that the BET specific surface area of ​​the adsorbent is 70-400 m 2 / g.

[0014] The third aspect of the present invention provides a porous carbon-supported metal oxide adsorbent prepared by the method described in the second aspect.

[0015] The fourth aspect of the present invention provides use of the adsorbent described in the first aspect or the third aspect in sewage treatment.

[0016] The present invention pyrolyzes solid waste in the presence of zinc chloride to obtain porous carbon, and loads metal oxides on the porous carbon. The formed adsorbent has a large specific surface area and pore volume, can quickly and effectively catalyze the removal of aniline in water, realizes the resource utilization of solid waste, has low preparation cost, and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the porous carbon-supported metal oxide adsorbent prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] In the present invention, unless otherwise specified, the room temperature or normal temperature refers to 25±2°C.

[0020] In the present invention, unless otherwise stated, the pressures described are gauge pressures.

[0021] In the present invention, unless otherwise specified, the oil content is measured according to standard HJ 1051-2019 infrared spectrophotometry.

[0022] As mentioned above, the first aspect of the present invention provides a porous carbon-loaded metal oxide adsorbent, which contains porous carbon and a metal oxide loaded on the porous carbon, wherein the porous carbon is obtained by pyrolysis of solid waste in the presence of zinc chloride, and the metal oxide is an oxide formed by at least one element of Fe, Co, Cu, and Ni; based on the total weight of the adsorbent, the content of the porous carbon is 88-95% by mass, and the content of the metal oxide is 2-8% by mass; the BET specific surface area of ​​the adsorbent is 70-400m 2 / g.

[0023] Preferably, in the adsorbent of the present invention, based on the total weight of the adsorbent, the remainder of the adsorbent is 3-6 mass % of oxides formed by at least one element of Si, Zn and Ca.

[0024] It should be noted that the oxide formed by at least one element of Si, Zn, and Ca described in the present invention does not play a major role in the catalytic degradation function of the adsorbent of the present invention, and these oxides are technologies known to those skilled in the art, and the present invention does not limit this, and those skilled in the art should not understand this as a limitation of the present invention.

[0025] Preferably, based on the total weight of the adsorbent, the content of the porous carbon is 89-92.5% by mass, and the content of the metal oxide is 2-7% by mass.

[0026] Preferably, the solid waste is a combination of solid residue and agricultural and forestry waste in a mass ratio of 1-10:1.

[0027] More preferably, in the solid waste, the mass ratio of the solid residue to the agricultural and forestry waste is 2-6: 1. The inventors found that in this preferred case, a porous carbon-supported metal oxide adsorbent with a larger specific surface area and pore volume can be obtained, and when the adsorbent is used to degrade aniline in water, a higher degradation rate can be obtained.

[0028] According to a particularly preferred embodiment of the present invention, the solid residue is selected from at least one of the solid residue after treatment of oily sludge, the solid residue after dehydration of municipal sludge, the solid residue after dehydration of refinery oil sludge, the solid residue after dehydration of refinery scum, and the solid residue after dehydration of refinery activated sludge.

[0029] Preferably, the oil content in the solid residue after the oily sludge treatment is 3-8wt%.

[0030] According to a particularly preferred embodiment of the present invention, the agricultural and forestry waste is selected from at least one of fruit shells, leaves, crop straws, rice straw, and wood chips.

[0031] The crop straw described in the present invention is at least one selected from wheat straw, sawdust, leaves and straw.

[0032] As mentioned above, the second aspect of the present invention provides a method for preparing a porous carbon-supported metal oxide adsorbent, the method comprising:

[0033] (1) subjecting solid waste and zinc chloride to a first contact mixing, and subjecting a first solid material obtained after the first contact mixing to a first pyrolysis to obtain porous carbon;

[0034] (2) contacting a metal salt solution with the porous carbon to perform an impregnation treatment, and performing solid-liquid separation on the impregnation mixture obtained after the impregnation treatment to obtain a solid impregnated product; wherein the metal element in the metal salt solution is selected from at least one of Fe, Co, Cu, and Ni;

[0035] (3) subjecting the solid impregnated material to a second pyrolysis and subjecting the second solid material obtained by the second pyrolysis to a molding process;

[0036] Wherein, the amount of the metal salt solution is such that the content of the metal oxide in the obtained porous carbon-supported metal oxide adsorbent is 2-8% by mass;

[0037] The conditions of the first pyrolysis and / or the second pyrolysis are controlled so that the BET specific surface area of ​​the adsorbent is 70-400 m 2 / g.

[0038] Preferably, in step (1), the mass ratio of the solid waste to the zinc chloride is 1:0.1-3.

[0039] According to a particularly preferred embodiment of the present invention, in step (1), the solid waste is a combination of solid residue and agricultural and forestry waste in a mass ratio of 1-10:1.

[0040] Preferably, in step (1), the conditions for the first contact mixing include at least: a temperature of 20-30° C. and a time of 1-180 min.

[0041] Preferably, in step (1), the conditions for the first pyrolysis include at least: a heating rate of 10-30°C / min, a temperature of 400-800°C, a protective atmosphere flow rate of 50-500mL / h, and a time of 1-3h.

[0042] Preferably, in step (1), the method further comprises: before performing the first contact mixing, pre-treating the solid waste to obtain solid waste with a moisture content ≯10wt% and an average particle size of 0.1-1mm.

[0043] According to a particularly preferred embodiment, in step (1), the pretreatment operation includes: drying and crushing the solid waste in sequence.

[0044] The present invention has no particular requirements for the specific method of crushing, as long as the solid waste with an average particle size of 0.1-1 mm can be obtained. For example, the dried solid waste can be ground to obtain solid waste with an average particle size of 0.1-1 mm.

[0045] Preferably, in step (1), the drying conditions at least include: a temperature of 90-120°C.

[0046] Preferably, in step (2), the metal salt solution is a cobalt salt aqueous solution and / or an iron salt aqueous solution.

[0047] According to a particularly preferred embodiment of the present invention, in step (2), the metal salt solution is a mixed aqueous solution of cobalt salt and iron salt.

[0048] Preferably, in step (2), in the metal salt solution, the mass ratio of the cobalt salt to the iron salt is 1:1-3.

[0049] Preferably, in step (2), the cobalt salt is selected from at least one of cobalt nitrate, cobalt acetate, cobalt sulfate and cobalt chloride.

[0050] Preferably, in step (2), the iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate.

[0051] Preferably, in step (2), the mass ratio of the porous carbon to the metal salt solution in terms of metal salt is 1:1-15.

[0052] Preferably, in step (2), the conditions for the immersion treatment include at least: a stirring speed of 50-400 rpm, a temperature of 20-40° C., and a time of 0.5-3 h.

[0053] Preferably, in step (2), the method further comprises: before performing the solid-liquid separation, adjusting the pH value of the impregnation mixture to 10-11.

[0054] The present invention has no special requirements for the method of adjusting the pH value, as long as the target pH value can be reached. The pH value can be adjusted using a conventional alkaline solution in the art. For example, the present invention uses a NaOH solution with a concentration of 1-3 mol / L to adjust the pH value of the impregnation mixture to 10-11.

[0055] Preferably, in step (3), the molding process comprises: contacting the second solid material with a binder and water and performing extrusion molding to obtain the porous carbon-supported metal oxide adsorbent.

[0056] Preferably, in step (3), relative to 100 g of the second solid material, the amount of the binder used is 20-50 g, and the amount of water used is 20-100 g.

[0057] According to a particularly preferred embodiment of the present invention, in step (3), the binder is selected from at least one of sodium carboxymethyl cellulose and starch.

[0058] Preferably, in step (3), the conditions for the second pyrolysis include at least: a heating rate of 10-30°C / min, a temperature of 100-200°C, a protective atmosphere flow rate of 50-500mL / h, and a time of 4-8h.

[0059] More preferably, in step (3), the conditions of the second pyrolysis at least include: a heating rate of 10-20°C / min, a temperature of 150-180°C, a protective atmosphere flow rate of 200-500mL / h, and a time of 5-8h. The inventors have found that by adopting the specific implementation of this preferred case, the porous carbon-supported metal oxide adsorbent obtained can achieve a higher degradation rate when used to degrade aniline.

[0060] Preferably, the protective atmosphere is selected from at least one of nitrogen, argon and carbon dioxide.

[0061] As mentioned above, the third aspect of the present invention provides a porous carbon-supported metal oxide adsorbent prepared by the method described in the second aspect.

[0062] As mentioned above, the fourth aspect of the present invention provides the use of the adsorbent described in the first aspect or the third aspect in sewage treatment.

[0063] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the raw materials used are commercially available products.

[0064] Solid residue-1: solid residue after the treatment of oily sludge, take 30g of oily sludge (water content 0.2wt%, solid content 28.14wt%, oil content 71.66wt%), add 90g of naphtha, and then add 180mL of NaOH aqueous solution (mass concentration 6wt%), then heat the mixture of the above-mentioned oily sludge, naphtha (i.e. light oil) and NaOH aqueous solution (i.e. detergent aqueous solution) to 60°C, stir magnetically (stirring rate is 180r / min) for 1 hour, and then centrifuge, take the lower layer of the centrifuge tube, and obtain solid residue-1 with an oil content of 3wt%;

[0065] Solid residue-2: solid residue after oily sludge treatment, the preparation method is similar to that of solid residue-1, except that the oil content is 5wt%;

[0066] Agricultural and forestry waste: wheat straw, collected from Guolu Village, Shiziyuan Town, Shen County, Liaocheng City, Shandong Province in August 2020. The wheat variety is the local Shenmai 818;

[0067] Among them, the moisture content of oily sludge is determined by the distillation method specified in the national standard GB / T 8929-2006;

[0068] The test method of the solid content of oily sludge is as follows: 3g of oily sludge is put into a crucible, the crucible is placed in a muffle furnace at 500°C, heated for 4 hours, taken out and placed in a drying dish, cooled to room temperature and weighed, the weight obtained is the solid content w in the oily sludge, to obtain the solid content of the oily sludge, wherein the calculation formula of the solid content is: (w / 3)×100%;

[0069] Oil content of oily sludge = 1 - water content of oily sludge - solid content of oily sludge;

[0070] In the following example, the agricultural and forestry waste is dried in an oven at 105° C. until the moisture content is ≯10 wt %, and then the agricultural and forestry waste is crushed and passed through a 40-mesh sieve to obtain agricultural and forestry waste powder with an average particle size of 0.4 mm for later use; and

[0071] The solid residue is dried in an oven at 105° C. until the moisture content is ≯10 wt %, and then the solid residue is ground and passed through a 40-mesh sieve to obtain a solid residue powder with an average particle size of 0.4 mm for later use;

[0072] In the following examples, the concentration of the NaOH solution is 2 mol / L.

[0073] Example 1

[0074] This embodiment provides a method for preparing a porous carbon-supported metal oxide adsorbent, the method comprising:

[0075] (1) At 25° C., 72 g of solid residue-1 and 24 g of wheat straw were mixed in a mass ratio of 3:1, 96 g of zinc chloride was added, and the mixture was mixed for 15 min to obtain a first solid material. The first solid material was placed in a quartz tube furnace, and the temperature was raised to 700° C. at a rate of 10° C. / min under nitrogen protection (nitrogen flow rate of 200 mL / min), and the temperature was kept constant for 2 h, and then naturally cooled to room temperature to obtain porous carbon;

[0076] (2) At room temperature, 2.91 g of cobalt nitrate and 8.08 g of ferric nitrate were added to 100 g of deionized water, and 10 g of porous carbon was added, and stirred at 200 rpm for 2 h, and then NaOH solution was added dropwise, and stirring was continued for 1 h. After the stirring was completed, the solid impregnation was filtered to obtain;

[0077] (3) placing the solid impregnated product in a tubular furnace, under nitrogen protection (nitrogen flow rate of 200 mL / min), raising the temperature from room temperature to 180° C. at a rate of 10° C. / min, reacting for 5 hours, and then naturally cooling to room temperature to obtain a second solid material;

[0078] (4) at room temperature, 10 g of the second solid material, 2 g of starch and 10 g of water were placed in a kneader and extruded at 40 MPa into a carbon strip having a diameter of 3 mm and a length of 2 cm to obtain a porous carbon-supported metal oxide adsorbent S1;

[0079] The porous carbon-supported metal oxide adsorbent S1 has a porous carbon content of 92.5% by mass, a cobalt content of 1.1% by mass, an iron content of 2.4% by mass, a silicon content of 1.2% by mass, a zinc content of 1.8% by mass, and a calcium content of 1.0% by mass. The product properties are shown in Table 1.

[0080] Example 2

[0081] In this example, a porous carbon-supported metal oxide adsorbent is prepared in a manner similar to that of Example 1, except that in step (2), 5.82 g of cobalt nitrate is used.

[0082] The remaining steps are the same as those in Example 1 to obtain the porous carbon-supported metal oxide adsorbent S2;

[0083] The porous carbon-supported metal oxide adsorbent S2 has a porous carbon content of 89.2% by mass, a cobalt content of 3.2% by mass in terms of oxide, an iron content of 3.6% by mass in terms of oxide, a silicon content of 1.3% by mass in terms of oxide, a zinc content of 1.7% by mass in terms of oxide, and a calcium content of 1.0% by mass in terms of oxide. The product properties are shown in Table 1.

[0084] Example 3

[0085] This example prepares a porous carbon-supported metal oxide adsorbent in a similar manner to that of Example 1, except that:

[0086] In step (1), at 25° C., 50 g of solid residue-2 and 10 g of wheat straw are mixed in a mass ratio of 5:1, 60 g of zinc chloride is added, and the mixture is mixed for 20 min to obtain a first solid material. The first solid material is placed in a quartz tube furnace, and the temperature is increased to 700° C. at a rate of 10° C. / min under nitrogen protection (nitrogen flow rate is 200 mL / min), and then the temperature is kept constant for 2 h, and the mixture is naturally cooled to room temperature to obtain porous carbon.

[0087] The remaining steps are the same as those in Example 1 to obtain porous carbon-supported metal oxide adsorbent S3;

[0088] The porous carbon-supported metal oxide adsorbent S3 has a porous carbon content of 92.7% by mass, a cobalt content of 1.3% by mass, an iron content of 2.8% by mass, a silicon content of 0.9% by mass, a zinc content of 1.5% by mass, and a calcium content of 0.8% by mass. The product properties are shown in Table 1.

[0089] Example 4

[0090] In this example, a porous carbon-supported metal oxide adsorbent is prepared in a manner similar to that of Example 1, except that in step (1), 192 g of solid residue-1 is used, i.e., the mass ratio of the solid residue to the agricultural and forestry waste is 8:1.

[0091] The remaining steps are the same as those in Example 1 to obtain porous carbon-supported metal oxide adsorbent S4;

[0092] The porous carbon-supported metal oxide adsorbent S4 has a porous carbon content of 91.8% by mass, a cobalt content of 0.9% by mass, an iron content of 2.1% by mass, a silicon content of 1.9% by mass, a zinc content of 1.7% by mass, and a calcium content of 1.6% by mass. The product properties are shown in Table 1.

[0093] Example 5

[0094] In this example, a porous carbon-supported metal oxide adsorbent is prepared in a manner similar to that of Example 1, except that in step (1), 24 g of solid residue-1 is used, i.e., the mass ratio of the solid residue to the agricultural and forestry waste is 1:1.

[0095] The remaining steps are the same as those in Example 1 to obtain porous carbon-supported metal oxide adsorbent S5;

[0096] The porous carbon-supported metal oxide adsorbent S5 has a porous carbon content of 92.3% by mass, a cobalt content of 0.8% by mass, an iron content of 1.9% by mass, a silicon content of 1.1% by mass, a zinc content of 3.0% by mass, and a calcium content of 0.9% by mass. The product properties are shown in Table 1.

[0097] Example 6

[0098] In this example, a porous carbon-supported metal oxide adsorbent is prepared in a manner similar to that of Example 1, except that in step (3), the temperature of the second pyrolysis is 350°C.

[0099] The remaining steps are the same as those in Example 1 to obtain the porous carbon-supported metal oxide adsorbent S6;

[0100] The porous carbon-supported metal oxide adsorbent S6 has a porous carbon content of 91.7% by mass, a cobalt content of 0.7% by mass in terms of oxide, an iron content of 1.7% by mass in terms of oxide, a silicon content of 2.2% by mass in terms of oxide, a zinc content of 1.9% by mass in terms of oxide, and a calcium content of 1.8% by mass in terms of oxide. The product properties are shown in Table 1.

[0101] Comparative Example 1

[0102] In this comparative example, a porous carbon-supported metal oxide adsorbent is prepared in a manner similar to that of Example 1, except that in step (2), 8.73 g of cobalt nitrate and 24.24 g of iron nitrate are used.

[0103] The remaining steps are the same as those in Example 1 to obtain the porous carbon-supported metal oxide adsorbent DS1.

[0104] The porous carbon-supported metal oxide adsorbent DS1 has a porous carbon content of 85.9% by mass, a cobalt content of 3.2% by mass in terms of oxide, an iron content of 6.8% by mass in terms of oxide, a silicon content of 1.2% by mass in terms of oxide, a zinc content of 1.8% by mass in terms of oxide, and a calcium content of 1.1% by mass in terms of oxide. The product properties are shown in Table 1.

[0105] Comparative Example 2

[0106] In this comparative example, a porous carbon-supported metal oxide adsorbent was prepared in a manner similar to that of Example 1, except that in step (2), 7.8 g of cobalt nitrate and 19.5 g of iron nitrate were used.

[0107] The remaining steps are the same as those in Example 1 to obtain porous carbon-supported metal oxide adsorbent DS2.

[0108] The porous carbon-supported metal oxide adsorbent DS2 has a porous carbon content of 87.1% by mass, a cobalt content of 2.9% by mass, an iron content of 5.8% by mass, a silicon content of 1.3% by mass, a zinc content of 1.7% by mass, and a calcium content of 1.2% by mass. The product properties are shown in Table 1.

[0109] Comparative Example 3

[0110] In this comparative example, a porous carbon-supported metal oxide adsorbent was prepared in a similar manner to Example 1, except that no second pyrolysis was performed, that is, the solid impregnated material was directly extruded with starch and water.

[0111] The remaining steps are the same as those in Example 1 to obtain porous carbon-supported metal oxide adsorbent DS3;

[0112] The porous carbon-supported metal oxide adsorbent DS3 has a porous carbon content of 94.7% by mass, a cobalt content of 0.31% by mass, an iron content of 0.69% by mass, a silicon content of 1.3% by mass, a zinc content of 1.8% by mass, and a calcium content of 1.2% by mass. The product properties are shown in Table 1.

[0113] Table 1

[0114]

[0115] As can be seen from Table 1, the present invention uses solid residues and agricultural and forestry wastes as carriers, and the iron-cobalt oxides are loaded on porous carbon by a post-impregnation method, so that the prepared porous carbon adsorbent has a large specific surface area and pore volume.

[0116] Test Case

[0117] The porous carbon-supported metal oxide adsorbent prepared in the examples and comparative examples was used to remove degraded aniline. The specific operation steps were as follows: 100 mL of aniline solution with a concentration of 20.0 mg / L was prepared, 0.5 g of the adsorbent prepared in the above examples or comparative examples was added thereto each time, and 15.2 g of potassium persulfate double salt (PMS) with a concentration of 1 mmol / L was added, and after reacting for 60 minutes, the degradation rate of aniline was calculated. The specific results are shown in Table 2.

[0118] The calculation formula of the degradation rate is: [(initial aniline concentration-aniline concentration after reaction) / initial aniline concentration]×100%.

[0119] Table 2

[0120] Degradation rate / % Example 1 80.6 Example 2 85.7 Example 3 93.5 Example 4 63.5 Example 5 45.9 Example 6 54.4 Comparative Example 1 30.7 Comparative Example 2 34.9 Comparative Example 3 40.4

[0121] It can be seen from Table 2 that the porous carbon-supported metal oxide adsorbent provided by the present invention can effectively degrade aniline in water, and the degradation rate of aniline is as high as 93.5% after 60 minutes.

[0122] The present invention exemplarily provides a scanning electron microscope image of the porous carbon-supported metal oxide adsorbent prepared in Example 1, see Figure 1 .

[0123] from Figure 1 It can also be seen that the porous carbon-supported metal oxide adsorbent prepared by the present invention has a large specific surface area and pore volume.

[0124] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a porous carbon-supported metal oxide adsorbent, characterized in that: The method includes: (1) subjecting solid waste and zinc chloride to a first contact mixing, and subjecting a first solid material obtained after the first contact mixing to a first pyrolysis to obtain porous carbon; (2) contacting the porous carbon with a metal salt solution to perform an impregnation treatment, and performing solid-liquid separation on the impregnation mixture obtained after the impregnation treatment to obtain a solid impregnated product; wherein the metal element in the metal salt solution is selected from at least one of Fe, Co, Cu, and Ni; (3) subjecting the solid impregnated material to a second pyrolysis and subjecting a second solid material obtained by the second pyrolysis to a molding process; The conditions of the second pyrolysis at least include: a heating rate of 10-30°C / min, a temperature of 100-200°C, a protective atmosphere flow rate of 50-500mL / min, and a time of 4-8h; Wherein, the amount of the metal salt solution is such that the content of the metal oxide in the obtained porous carbon-supported metal oxide adsorbent is 2-7% by mass; Based on the total weight of the adsorbent, the content of the porous carbon is 89.2-92.7% by mass; In step (1), the solid waste is a combination of solid residue and agricultural and forestry waste in a mass ratio of 3-6:1; The conditions of the first pyrolysis and / or the second pyrolysis are controlled so that the BET specific surface area of ​​the adsorbent is 70-400 m 2 / g; The solid residue is selected from at least one of the solid residue after oily sludge treatment, the solid residue after municipal sludge dehydration, the solid residue after refinery oil sludge dehydration, the solid residue after refinery scum dehydration, and the solid residue after refinery activated sludge dehydration; The oil content of the solid residue after the oily sludge treatment is 3-8wt%.

2. The method according to claim 1, wherein: In step (1), the mass ratio of the solid waste to the zinc chloride is 1:0.1-3.

3. The method according to claim 1 or 2, wherein: In step (1), the first contact mixing conditions at least include: a temperature of 20-30°C.

4. The method according to claim 1 or 2, wherein: In step (1), the conditions for the first pyrolysis include at least: a heating rate of 10-30°C / min, a temperature of 400-800°C, a protective atmosphere flow rate of 50-500mL / h, and a time of 1-3h.

5. The method according to claim 1 or 2, wherein: In step (1), the method further comprises: before the first contact mixing, pre-treating the solid waste to obtain solid waste with a moisture content of ≯10wt% and an average particle size of 0.1-1mm.

6. The method according to claim 1 or 2, wherein: In step (2), the metal salt solution is a cobalt salt aqueous solution and / or an iron salt aqueous solution.

7. The method according to claim 1 or 2, wherein: In step (2), the metal salt solution is a mixed aqueous solution of cobalt salt and iron salt.

8. The method according to claim 7, wherein: In step (2), in the metal salt solution, the mass ratio of the cobalt salt to the iron salt is 1:1-3.

9. The method according to claim 7, wherein: In step (2), the cobalt salt is selected from at least one of cobalt nitrate, cobalt acetate, cobalt sulfate and cobalt chloride.

10. The method according to claim 7, wherein: In step (2), the iron salt is selected from at least one of ferric chloride, ferric nitrate and ferric sulfate.

11. The method according to claim 1 or 2, wherein: In step (2), the mass ratio of the porous carbon to the metal salt solution in terms of metal salt is 1:1-15.

12. The method according to claim 1 or 2, wherein: In step (2), the conditions for the immersion treatment include at least: a stirring speed of 50-400 rpm, a temperature of 20-40° C., and a time of 0.5-3 h.

13. The method according to claim 1 or 2, wherein: In step (2), the method further comprises: before performing the solid-liquid separation, adjusting the pH value of the impregnation mixture to 10-11.

14. The method according to claim 1 or 2, wherein: In step (3), the molding process includes: contacting the second solid material with a binder and water and performing extrusion molding to obtain the porous carbon-supported metal oxide adsorbent.

15. The method according to claim 14, wherein: In step (3), relative to 100 g of the second solid material, the amount of the binder used is 20-50 g, and the amount of water used is 20-100 g.

16. The method according to claim 15, wherein: In step (3), the binder is selected from at least one of sodium carboxymethyl cellulose and starch.

17. The method according to claim 1, wherein: The protective atmosphere is selected from at least one of nitrogen, argon and carbon dioxide.

18. A porous carbon-supported metal oxide adsorbent prepared by the method according to any one of claims 1 to 17.

19. Use of the adsorbent according to claim 18 in sewage treatment.

Citation Information

Patent Citations

  • Method for preparing adsorbing material from oil sludge residues and application thereof

    CN111167408A

  • Oil sludge carbon supported metal catalyst, and preparation method and application thereof

    CN110548515A

  • Oily sludge-based biochar as well as preparation method and application thereof

    CN114517104A